Cardiovascular adverse events associated with cyclophosphamide, pegylated liposomal doxorubicin, vincristine, and prednisone with or without rituximab ((R)-CDOP) in non-Hodgkin’s lymphoma: A systematic review and meta-analysis - Lu, Bin; Shen, Longfei; Ma, Ying; Qi, Jia; Li, Yulin; Wang, Zhihao; Han, Lu; Zhong, Ming (Frontiers in Pharmacology, 2022)
Background: The (R)-CDOP combination regimen, based on pegylated liposomal doxorubicin, is increasingly used in elderly patients with non-Hodgkin’s lymphoma. However, the cardiotoxicity and efficacy of the (R)-CDOP regimen compared with conventional anthracyclines has not been demonstrated in the general population. Methods and Results: PubMed, Embase, Cochrane Library, CNKI, WanFang Database, and VIP were searched. The important findings were as follows: total cardiovascular event rate, 7.45% (95% confidence interval [CI] = 4.86%–10.44%); non-serious cardiovascular adverse event rate, 6.48% (95% CI = 3.70%–9.8%); serious cardiovascular adverse event rate, 0.67% (95% CI = 0.00%–2.12%); heart failure rate, 0.55% (95% CI = 0.00%–1.93%); rate of treatment discontinuation attributable to left ventricular dysfunction or heart failure, 0.02% (95% CI = 0.00%–0.57%); and cardiovascular death rate, 0.00% (95% CI = 0.00%–0.37%). Compared with the (R)-CHOP regimen, the (R)-CDOP regimen reduced the risk of cardiovascular events, including total cardiovascular adverse events (odds ratio [OR] = 0.161, 95% CI = 0.103–0.251, p < 0.001, NNT = 3.7), non-serious cardiovascular adverse events (OR = 0.171, 95% CI = 0.093–0.314, p < 0.001, NNT = 3.6), serious cardiovascular adverse events (OR = 0.252, 95% CI = 0.119–0.535, p < 0.001, NNT = 6.8), and heart failure (OR = 0.294, 95% CI = 0.128–0.674, p = 0.004, NNT = 9.5). We found the (R)-CDOP regimen was no less efficacious, including complete remission (CR) (OR = 1.398, 95% CI = 0.997–1.960, p = 0.052), partial response (PR) (OR = 1.631, 95% CI = 1.162–2.289, p = 0.005), objective response rate (ORR) (OR = 2.236, 95% CI = 1.594–3.135, p < 0.001), stable disease (SD) (OR=0.526, 95% CI = 0.356–0.776, p = 0.001) and progressive disease (PD) (OR=0.537, 95% CI = 0.323–0.894, p = 0.017). Conclusion: Our findings suggested that the (R)-CDOP regimen had a lower risk of cardiovascular adverse events in non-Hodgkin’s lymphoma than the (R)-CHOP regimen, demonstrating its safety concerning cardiotoxicity. In addition, this study found the (R)-CDOP regimen was no less efficacious than (R)-CHOP regimen in the treatment of non-Hodgkin’s lymphoma. These findings need to be validated by higher-quality research because of the limited number and quality of included studies.